Influence of teichoic acid from S. Aureus on metabolic activity of macrophages and cytotoxic activity of splenocytes of mice bearing Lewis lung carcinoma - Potebnya, G.P.; Skivka, L.M.; Pozur, V.V.; Rudik, M.P.; Senchilo, N.V.; Fedorchuk, O.G.; Khranovska, N.M. (Experimental Oncology, 2008)
To investigate the effect of teichoic acid (TA) from the cell wall of S. aureus on some indices of immunological reactivity in mice bearing Lewis lung carcinoma (LLC). Methods: The teichoic acid at the doses of 1, 2 and 4 µg/g of body weight has been administered subcutaneously simultaneously with tumor cells transplantation and in 7 days. The cytotoxic activity of peritoneal macrophages has been assessed by NBT-test. The splenocyte cytotoxic activity against the LLC cells has been tested by flow cytometry. The evaluation of tumor infiltration by lymphoid cells was carried out as well. Results: TA had no significant effect on oxidative metabolism of peritoneal macrophages in tumor bearing mice. Upon TA administration, the cytotoxic activity of splenocytes against the LLC cells has been augmented in a dose-dependent manner (at the TA dose of 4 µg/g, 2-fold decrease of tumor growth and metastasis has been registered) and leads to decreased tumor infiltration by mononuclear cells. Conclusion: TA caused a dose dependent inhibition of growth and metastasis of LLC. It was supposed that TA can influence the tumor grows by activation of splenocytes cytotoxic activity.